(3YfhGf GdEaGOI dENhGf GdGSJaGOIs - (3CHhYHO Gddg TeS GdOjf eMeO Hf eMeO Hf eMeO Hf ESeGYjd GdCfOdSj GdeYQha HGdQGYjs; (3GHf BoLoqQhe, eMeO Hf eMeO Hf OGhO GdUfgGLj, CHh YHO Gddg,J (B723 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEfg deG cGf Yde GdYQHjI ef CYXe GdYdhe hjaQb Hg Hjf GdUMjM hGdSbje ef GdcdGe s
(3BNQgG (B:s
(3bhdge eVGa Edjg hajg VejQ eaYhd de jSe aGYdg jYhO Ydi GdcdGe, hEdjg jJYdb HGSe GdeaYhd s
(3HgG fXGe GdJYbjHIs
(3aj GdeYgO fSNI CNQi GfXQgG aj GdLRA GdChd HQbe (B113 (3fMhs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs